Data from: Evidence for varying social strategies across the day in chacma baboons - Sick, Claudia; Carter, Alecia J.; Marshall, Harry H.; Knapp, Leslie A.; Dabelsteen, Torben; Cowlishaw, Guy (Dryad, 2014)
Strong social bonds can make an important contribution to individual
fitness, but we still have only a limited understanding of the temporal
period relevant to the adjustment of social relationships. While there is
growing recognition of the importance of strong bonds that persist for
years, social relationships can also vary over weeks and months,
suggesting that social strategies may be optimized over shorter
timescales. Using biological market theory as a framework, we explore
whether temporal variation in the benefits of social relationships might
be sufficient to generate daily adjustments of social strategies in wild
baboons. Data on grooming, one measure of social relationships, were
collected from 60 chacma baboons (Papio ursinus) across two troops over a
six month period. Our analyses suggest that social strategies can show
diurnal variation, with subordinates preferentially grooming more dominant
individuals earlier in the day compared with later in the day. These
findings indicate that group-living animals may optimize certain elements
of their social strategies over relatively short time periods.
Data used in Sick et al 2014Sicketal2014data.csv
Keywords: social strategies; biological market; Papio ursinus; baboon